2011
DOI: 10.1074/jbc.m111.277152
|View full text |Cite
|
Sign up to set email alerts
|

Mas-related Gene X2 (MrgX2) Is a Novel G Protein-coupled Receptor for the Antimicrobial Peptide LL-37 in Human Mast Cells

Abstract: Background: Antimicrobial peptide LL-37 activates leukocytes, mast cells, and endothelial cells. Results: LL-37 causes chemotaxis, degranulation, and chemokine production in human mast cells expressing MrgX2, but it does not induce receptor desensitization. Conclusion: MrgX2 is a novel receptor for LL-37 in human mast cells, and this receptor is resistant to regulation. Significance: This study has important implications for innate immunity and inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
241
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(255 citation statements)
references
References 57 publications
8
241
0
Order By: Relevance
“…SP activates MrgprB2, MrgprA1, and MRGPRX2 in addition to NK-1R; Mrgprs have otherwise been considered orphan receptors. MRGPRX2 can be activated by a number of peptides, including cortistatin-14, the proadrenomedullin C-terminal peptides PAMP-12 and -20, and LL-37, but physiological consequences have not been identified (12,13,34).…”
Section: Discussionmentioning
confidence: 99%
“…SP activates MrgprB2, MrgprA1, and MRGPRX2 in addition to NK-1R; Mrgprs have otherwise been considered orphan receptors. MRGPRX2 can be activated by a number of peptides, including cortistatin-14, the proadrenomedullin C-terminal peptides PAMP-12 and -20, and LL-37, but physiological consequences have not been identified (12,13,34).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-oxidation are vital substances which possess the ability to protect the body from damage caused by free radicals inducing oxidative stress [28]. Antioxidant compounds like phenolic acids, polyphenols and flavonoids scavenge free radicals such as peroxide, hydroperoxide of lipid hydroxyl and halt the oxidative mechanism that leads to degenerative diseases [29]. Flavonoids are proactive polyphenolic compounds found in most plants and cannot be synthesized or produced by the humans [30].…”
Section: Discussionmentioning
confidence: 99%
“…The immunomodulatory effects of LL-37 have been ascribed to its binding to and/or modulating activity of several unrelated cell surface receptors such as FPRL 1, EGFR, P2X 7 , and others. 12,[16][17][18][19]42 In this study, we demonstrated that LL-37 is a ligand for the major integrin receptor Mac-1 (CD11b/CD18) on the surface of myeloid cells and found that coating of bacteria with LL-37 augments Mac-1-mediated …”
Section: Discussionmentioning
confidence: 96%
“…However, the mechanisms underlying these LL-37 responses have not been well characterized, and to date, several receptors were reported to associate with LL-37-induced immunomodulation. 12,[16][17][18][19] We have recently characterized the recognition specificity of integrin a M b 2 (Mac-1, CD11b/CD18), a receptor with broad ligand-binding specificity expressed on neutrophils and monocyte/macrophages, and identified structural motifs present in many Mac-1 ligands. 20 In particular, the a M I-domain, a ligand-binding region of Mac-1, has affinity for short 6-9 mer amino acid sequences containing a core of basic residues flanked by hydrophobic residues in which negatively charged residues are strongly disfavored.…”
Section: +mentioning
confidence: 99%